Toward a critical posthuman understanding of teacher development and practice: A multi-case study of beginning teachers. (June 2022) - Strom, Kathryn J.; Martin, Adrian D.
Abstract: The purpose of this paper is to theorize an alternative, non-linear conceptualization of beginning teacher development based on critical posthumanism, which we illustrate through analysis from three in-depth case studies of first-year science teachers in the U.S. Drawing on the conceptual tools of assemblage, distributive agency, and intra-action, we examine three complex, relational processes that first-year teachers engaged in to construct their teaching practices: translating their pre-professional learning into practice, negotiating with students, and forming their teacher subjectivity. We argue that this framework offers potential for better preparing and supporting new teachers in diverse national settings as well as interrupting the patterns of inequities that are perpetuated through structures of schooling, dominant forms of pedagogy, and deficit-based interactions with students.